Comparison of Antioxidant Activity and Chemical Profile between Green Tea Kombucha with Green Tea and Rosela Combination Kombucha - Tunjungsari, Gerda Pintoko; Fikroh, Retno Aliyatul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study investigates the antioxidant potential and chemical profile of kombucha made from green tea leaves and roselle flowers, analyzing pH, alcohol content, and the impact of fermentation time. Kombucha was prepared with green tea and a 1:1 mixture of green tea and roselle, with samples analyzed on days 1, 4, 8, 12, 16, and 24. Antioxidant activity, pH, and alcohol content were measured, and statistical analyses including one-way ANOVA, Tukey HSD, and Spearman correlation tests were conducted. Results indicated that the combination kombucha exhibited higher antioxidant activity (96.39% DPPH inhibition) compared to green tea kombucha (79.62%). There was no significant difference in pH and alcohol content between the two types (p > 0.05). A strong negative correlation was found between pH and fermentation time (-0.589, p < 0.001) and pH and alcohol content (-0.571, p < 0.001), while a strong positive correlation was observed between % inhibition and fermentation time (0.637, p < 0.001). The findings suggest that combining green tea and roselle enhances antioxidant activity in kombucha, and fermentation time significantly affects antioxidant activity, pH, and alcohol content.